Perception Of Housekeeping As A Career Amongst Hotel Management Students ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Hotel industry is contributing a magnificent proportion to the country’s economy  because of the exponential growth in travel. Whatever is the guest’s preference but the first and  foremost requirement of all is high standards of cleanliness and hygiene. All the professionals from  the industry nod for this undoubted fact but still the hotel management students are not motivated  to select housekeeping as a profession. Objectives: To determine the root cause of housekeeping  not being selected as a career by the majority of hotel management students. It also focuses on the  factors that lead to disinterest for housekeeping amongst the students. Methodology: The study  was conducted in the top Hotel Management institutes of Chandigarh, Punjab, Delhi and Haryana.  The data collection was based on questionnaires and interviews of final year students of respective  institutes. Results: Only 20% of students were found to be opting for housekeeping as their career.  The main reason given by students for not liking housekeeping subject were menial cleaning tasks  involved for example bathroom cleaning and public area cleaning. The study clearly showed that 1st year syllabus creates an impression of housekeeping being a menial and monotonous subject which  majorly is cleaning and this mindset then becomes difficult to change. 21% felt that housekeeping  offers lower pay scale. Conclusion: The study found out the various reasons for making this subject  unfit due to lack of communication skills, less training required etc. and the various reasons behind  not selecting housekeeping as career like job nature, poor salary, delayed promotions, lack of  creativity and monotony, lack of esteem etc.
Keywords: Housekeeping; Profession; Students; Placements; Career; Economy